Solar Cells: Solvent Additive Effects on Small Molecule Crystallization in Bulk Heterojunction Solar Cells Probed During Spin Casting (Adv. Mater. 44/2013). (26th November 2013) - Perez, Louis A.; Chou, Kang Wei; Love, John A.; van der Poll, Thomas S.; Smilgies, Detlef‐M.; Nguyen, Thuc‐Quyen; Kramer, Edward J.; Amassian, Aram; Bazan, Guillermo C.
<x xml:space="preserve">Abstract</x> In situ X‐ray scattering is used by Guillermo C. Bazan, Aram Amassian and co‐workers to investigate the kinetics of crystallization during spincasting of an organic bulk‐heterojunction (BHJ) layer based on a small molecule‐fullerene blend, as described on page 6380. The high‐speed measurements capture evidence of an unexpected structural evolution and phase transformation of the small‐molecule donor both during and shortly after spin‐casting; such behavior is not known to occur in polymer‐fullerene BHJ solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>